Online, Offline, Flexible: Instructional Delivery Preferences of Pre-service Teachers in College Genetics and Its Implications for Curriculum, Instruction and Assessment - Jun S. Camara (Universitas Sultan Ageng Tirtayasa, 2023)
Learning curricula are designed to be needs-focused but are expected to be learner-friendly nonetheless. This study aimed to measure the level of instructional delivery preferences of undergraduate students in an introductory Genetics course (online, offline, flexible) and determined the influence of gender, year level, and post-secondary track. Using a descriptive survey approach, a list of genetics undergraduate topics were prepared based on various sources including university syllabi, textbooks, and other instructional materials. The questionnaire was administered digitally to undergraduate students in one large public university in mid-2021. Findings report that a genetics undergraduate course is preferred to be delivered ‘Highly Online’ with a few topics agreed upon by respondents as ‘Flexible’. On the contrary, teacher-experts prefer the course to be delivered in a ‘Flexible Manner’ with most of the topics to be delivered ‘Highly Offline’. Further, the student-respondents in any year level did not have any significant difference in their instructional delivery preferences in the listed topics, while a few topics’ instructional delivery preferences were viewed differently statistically by female respondents and those who graduated from non-STEM tracks in senior high school favoring such topics with ‘Highly Online’. Implications are drawn from the findings to better understand its influence to undergraduate curriculum, college instruction, and student learning assessment.